Ethnomathematics-Based Flipbook Media in Mathematics Content on Flat Building Materials for Grade I Elementary School - I Nyoman Gede Raka Adi Sunantara; Anak Agung Gede Agung; I Wayan Wiarta (Universitas Pendidikan Ganesha, 2024)
Mathematics learning on the subject of flat shapes has been ineffective because it still predominantly uses the lecture method with textbooks, so that student motivation and understanding are not optimal. This study aims to analyze the effectiveness of ethnomathematics-based flipbook media in improving students' understanding of two-dimensional shapes in first-grade elementary school. This is a development study using the ADDIE model. The research subjects include subject matter experts, design experts, educational media experts, and 28 first-grade students as the experimental sample. Data were collected through questionnaires and comprehension tests, then analyzed using quantitative descriptive techniques and inferential statistical analysis. The media design received a score of 90.90%, while evaluations by experts and users indicated very good qualifications in terms of content, instructional design, and media. Individual and small group trials yielded positive responses and very good qualifications. Effectiveness analysis using statistical tests showed significant differences between learning outcomes before and after using the media. These findings indicate that ethnomathematics-based flipbook media are effective in improving students' understanding of flat shapes. The implications of this research are that such media can be used as effective learning tools for mathematics in elementary schools.